Peran Komite Sekolah dalam Peningkatan Mutu Sekolah MIS Muhammadiyah Dumeling Kecamatan Wanasari Kabupaten Brebes - Widyawan, Hadi; Abdullah, Ghufron; Ginting, Rosalina Br. (PGRI Kota Semarang, 2024)
This research aims to describe and analyze: The role of the School Committee in Improving School Quality (1) The role of the School Committee as an advisor (2) The role of the School Committee as a supporter of the school (3) The role of the School Committee as a controller, and (4) The role of the School Committee as school mediator. This research uses a qualitative approach with a qualitative type. Data were collected using interviews, observation and documentation methods, while data validation was carried out through triangulation. This research uses a qualitative approach with a case study type. Data were collected using interviews, observation and documentation methods, while data validation was carried out through triangulation. The results of this research show that the MIS Muhammadiyah Dumeling School Committee carries out four main roles to improve school quality. As advisors, they develop teaching and learning processes, co-curricular and extra-curricular programs. As supporters, they are actively present at school, provide creative and innovative ideas, and form parent/guardian associations. As controllers, they intensively monitor school finances, the performance of school principals, educators and education staff at the end of each school year, as well as school conditions on a regular basis. As mediators, they create family and educational relationships, bridge the interests of schools and parents, and provide interactive communication channels both directly and online. The author suggests that school principals are expected to continue to optimize the role of school committees to improve school quality by maintaining good communication so that committees can participate and contribute significantly to efforts to improve the quality of education. Appropriate policies from the school principal are very important to support the success of all learning programs and activities. Teachers are also expected to actively engage with the committee, not only through the principal, as well as optimize the participation of the parent association which supports the committee in their respective classes. Apart from that, teachers are expected to continue to improve their performance and competence to meet parents' expectations.